Poly(phenylene sulfide) derivatives as ultralow dielectric loss materials with stable frequency response - Seigo Watanabe; Shuma Miura; Tomohiro Miura; Yoshino Tsunekawa; Daisuke Ito; Kenichi Oyaizu (Communications Materials)
Abstract With the recent high-speed telecommunication technologies, polymers with low dielectric constants (D k) and low dissipation factors (D f) have been in demand. However, the lack of rational molecular designs simultaneously satisfying both low D k and low D f hinders further exploration of low-dielectric polymers. Herein, we present a class of sulfur-containing aromatic polymers, namely poly(phenylene sulfide) (PPS) derivatives, as a promising family satisfying ultralow dielectric loss. In particular, poly(2,6-dimethyl-1,4-phenylene sulfide) (PMPS) exhibits an exceptionally low D f (0.00087) at 10 GHz due to its amorphous nature and the small dipoles of the sulfide groups, while exhibiting a low D k (2.80) despite the presence of polarizable sulfur. What is more, the alternating PMPS-poly(2,6-dimethyl-1,4-phenylene oxide) (PPO) copolymer anomalously maintains robust low dielectric properties over a wide frequency range, featured by a low D k (~2.7) and an ultralow D f (<0.002) even in 10–80 GHz. Comprehensive investigations revealed that these stable dielectric properties originated from a sulfur-oxygen alternating sequence, leading to the biased dipoles satisfying intermolecular electrostatic interactions, thereby preventing molecular motions even at higher frequencies.